(untitled) (Revista "Boletín el Conuco", 2022)
This article presents a study developed with a descriptive methodology and a quantitative observation analysis method on the procedure for preparing the Annual Operational Investment Plan (POAI) in the municipal mayor’s office of Villavicencio. The methodological guides available from the National Planning Department (DNP) are used as a basis, which parameterize the formulation of procedures of the entities and allow the periodic evaluation of the financial statements and the progress of the Municipal Development Plan. The main objective is to analyze the performance of the municipal administration in the planning process for the formulation of the POAI and generate recommendations that optimize the results in the execution of resources against the municipal investment projects that rest in the BPIM Program Bank by analyzing the Available data for the 2020-2023 period. The quantitative analysis used allowed us to determine that the execution of resources of the municipal administration “Villavicencio Cambia Contigo 2020-2023” presents results of improvement in compliance with the POAI compared to the same validity of previous years, however, some programs presented delays in their executions, so it was determined that improving the POAI preparation procedure involves articulating the Development Plan with the Budget System. As a main conclusion, it is established that it is necessary to insert financial analyzes with an early warning system during the monthly and quarterly reports that emerge from the PAOI, which allows the municipal administration to improve its budget performance at the end of the periods.